Inverse Scattering on the Half Line for the Matrix Schrödinger Equation - Aktosun, Tuncay; Weder, Ricardo (Журнал математической физики, анализа, геометрии, 2018)
The matrix Schrödinger equation is considered on the half line with the general selfadjoint boundary condition at the origin described by two boundary matrices satisfying certain appropriate conditions. It is assumed that the matrix potential is integrable, is selfadjoint, and has a finite first moment. The corresponding scattering data set is constructed, and such scattering data sets are characterized by providing a set of necessary and sufficient conditions assuring the existence and uniqueness of the one-toone correspondence between the scattering data set and the input data set containing the potential and boundary matrices. The work presented here provides a generalization of the classic result by Agranovich and Marchenko from the Dirichlet boundary condition to the general selfadjoint boundary condition. На пiвпрямiй розглянуто матричне рiвняння Шредiнгера iз загальною самоспряженою крайовою умовою в нулi, яка задається двома матрицями, що задовольняють певнi умови. Вважається, що матричний потенцiал є самоспряженим, iнтегровним та має скiнченний перший момент. Побудовано вiдповiдну множину даних розсiяння. Цю множину даних розсiювання характеризовано набором необхiдних i достатнiх умов, якi гарантують єдинiсть та взаємно однозначну вiдповiднiсть мiж множиною даних розсiяння та множиною вхiдних даних, яка мiстить потенцiал та крайовi матрицi. Ця робота надає узагальнення з крайової умови Дiрiхле на загальну самоспряжену крайову умову для класичного результату Аграновича та Марченка.